2011
DOI: 10.1021/bm2004675
|View full text |Cite
|
Sign up to set email alerts
|

Macromolecular Design of Aliphatic Polyesters with Maintained Mechanical Properties and a Rapid, Customized Degradation Profile

Abstract: An innovative type of triblock copolymer that maintains and even increases the mechanical properties of poly(l-lactide) (PLLA) and poly(ε-caprolactone) (PCL) with a controlled, predictable, and rapid degradation profile has been synthesized. Elastic triblock copolymers were formed from the hydrophobic and crystalline PLLA and PCL with an amorphous and hydrophilic middle block of poly(but-2-ene-1,4-diyl malonate) (PBM). The polymers were subjected to degradation in PBS at 37 °C for up to 91 days. Prior to degra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 29 publications
1
18
0
Order By: Relevance
“…We have in previous work shown that the triblock copolymer of PBM and PLLA degrades by a rapid initial hydrolysis in the amorphous PBM middle block forming two diblock copolymers, where after the degradation profile follows that of the homopolymer of PLLA with similar molecular weight. [20] This was also accompanied with a significant reduction in ductility and molecular weight. The molecular weight of the homopolymer of PBM decreased much more slowly and 90% remained after 28 d of degradation.…”
Section: Changes In Materials Properties and Phmentioning
confidence: 98%
See 1 more Smart Citation
“…We have in previous work shown that the triblock copolymer of PBM and PLLA degrades by a rapid initial hydrolysis in the amorphous PBM middle block forming two diblock copolymers, where after the degradation profile follows that of the homopolymer of PLLA with similar molecular weight. [20] This was also accompanied with a significant reduction in ductility and molecular weight. The molecular weight of the homopolymer of PBM decreased much more slowly and 90% remained after 28 d of degradation.…”
Section: Changes In Materials Properties and Phmentioning
confidence: 98%
“…The triblock copolymer retained its mechanical properties for a specific time period and then degraded via a rapid initial hydrolysis. [20] We have The pre-polymer poly(but-2-ene-1,4-diyl malonate) (PBM) and a series of PBM-based materials are shown to be degradable under physiological conditions in vitro and they are therefore presented as potential materials for biomedical applications. Four different PBM-based materials are synthesized: a PBM homopolymer, crosslinked PBM with and without spacer, and a triblock copolymer of PBM and PLLA with the PBM as an amorphous middle block.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, when the polymer chains are short enough, the increased mobility of the chains makes it possible for them to reorganize and crystallize [40,45]. The melting temperature for films degraded at pH 1 decreased (from 66 to 64 C) as a result of the formation of smaller crystals of shorter polymer chains [46].…”
Section: Differential Scanning Calorimetry (Dsc)mentioning
confidence: 99%
“…Some of the explored systems include central blocks of 1,5-dioxepan-2-one (DXO), ε-caprolactone (CL), poly(but-2-ene-1,4-diyl malonate) (PBM) and ε-decalactone (DL) [13,17e20]. Specifically, fast hydrolyzable block modules of either poly(1,5-dioxepan-2-one) (PDXO) [13] or poly(-but-2-ene-1,4-diyl malonate) (PBM) [20] have shown gradual or rapid hydrolysis profiles, respectively. In contrast, slow degrading blocks of either poly(ε-caprolactone) (PCL) or poly(ε-decalactone) (PDL) have been demonstrated to severely reduce the hydrolysis rates of the triblock materials [19].…”
Section: Introductionmentioning
confidence: 99%